Pelatihan Membacakan Puisi Siswa MTSS.TI Ranah - Nur, Hidayatun; Hermaliza, Hermaliza; Latif, Latif; Mukhlis, Muhammad; Ersalinda, Dila; Rainov Ardi, Veronika (UIR Press, 2026)
This community service activity was motivated by the low poetry-reading skills of students at MTSS TI Ranah, characterized by weak intonation, expression, articulation, and self-confidence. Limited learning facilities influenced this condition, the absence of structured poetry-reading training, and a lack of qualified Indonesian-language teachers. The activity used a performance-based learning approach to improve students’ poetry-reading skills through systematic training and direct practice. Data were collected using observation, interviews, questionnaires, and documentation during the implementation of the training program. Data analysis was conducted using qualitative and quantitative descriptive techniques to examine changes in students’ performance and participants’ responses to the activity. The results showed a significant improvement in students’ poetry-reading skills after the training, particularly in intonation, expression, articulation, pauses, and emotional engagement. Students also demonstrated increased confidence and enthusiasm in performing poetry in front of others. In conclusion, performance-based learning proved to be a practical approach for enhancing poetry Reading skills and fostering students’ appreciation of literary performance in Indonesian language learning.